IMPLEMENTASI ART THERAPY UNTUK MENINGKATKAN COPING STRESS TERKAIT PERMASALAHAN PERKEMBANGAN DI USIA REMAJA - Putri, Dhian Riskiana; Fillianto, Anindra Desfi Chantika; Iriyanto, Jagad Banabsyah (JURNAL TALENTA PSIKOLOGI, 2021)
Adolescence is a vulnerable condition because adolescents are in a transition period from children to adults. There are many problems experienced by adolescents related to development that occur in physical, cognitive, social, and psychoemotional aspects. Adolescent problems include: identity confusion, conflict with parents, competition between groups, juvenile delinquency, and so on, which if it drags on can cause stress. One of the efforts to reduce and overcome stress is through art therapy. Art therapy is a therapy that uses art as an intermediary medium. Art therapy is able to visually communicate thoughts and feelings that are too painful to be included in works of art. Art therapy in the form of writing, drawing, painting and making objects from clay. This article aims to summarize various previous studies which can then be used as a deepening and theory development regarding the implementation of art therapy to increase coping stress related to developmental problems in adolescence. The research method used is library research (library research). Based on the results of the collection of 9 literature studies related to stress coping in adolescents with the art therapy method, all of them state that; art therapy can reduce anxiety, stress, or mental disorders felt by adolescents.